Pristup dizajniranju ISDN marketinškog miksa - Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
Initial ’commercial’ ISDN marketing-mix applications confirm the import of marketing in successful implementation of ISDN. Within insufficiently researched complex of ISDN marketing issues the paper presents the concept of the required more vigorous optimal marketing of ISDN on line with the actual environment and requirements of the users. Promotion activities in such approach are only part of marketing instruments. The paper initially defines the basic ISDN marketing-mix variables with some relevant elements and respective attributes. On the level of aggregate variables an optimal model has been proposed which suggests a more efficient combination of ISDN marketing-mix. Modular aspect, flexibility of technical and technological solutions and regulatory control increases the scope of optimal marketing.